Zebrafish in Biomedical Research - Bozkurt, Yusuf (IntechOpen, 2020)
The zebrafish (Danio rerio) is one of the best animal models to understand biological mechanisms and develop new methods for treating some human diseases. In this framework, the zebrafish is a versatile animal model organism for many research fields because of its many advantages, including rapid embriyonic development, easy maintenance and transparency of its embryos. Zebrafish in Biomedical Research describes the current understanding of zebrafish as a model organism in biomedical science. Written by experts in the field, this volume discusses the potential use of zebrafish in neurological diseases such as Alzheimer's and Parkinson's, in respiratory and kidney diseases, and in developing new drugs.